Guarding expertise and assets: Non-competition agreements and their implications - Adam Feher (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2024)
The degree of access granted to employees to a firm's critical asset is a pivotal organizational decision. This access can boost the employees' productivity within the firm but also enables them to become competitors after leaving, leading to a holdup problem. Economic theory suggests that non-competition agreements (noncompetes) can mitigate this issue. This paper examines the optimal compensation package for an employee, considering access, wage, and noncompete agreements. I demonstrate that firms compensate lower ability agents primarily through access, coupled with the minimum wage and strictest noncompete agreements since access not only increases the employee's utility but also the firm's production. For higher ability agents, the maximum degree of access is provided, while the wage and stringency of the noncompete depends on the damage the employee causes with competing. For low damages, the firm offers a lax noncompete with lower wages. Conversely, high potential damage necessitates higher wages and a stricter noncompete. The study's findings are consistent with observed patterns in CEO contracts.
Keywords: 330